Quantifying the distinct role of plasmon enhancement mechanisms in prototypical antenna-reactor photocatalysts - Shuang Liu; Zhiyi Wu; Zhijie Zhu; Kai Feng; Yuxuan Zhou; Xinge Hu; Xiong Huang; Binbin Zhang; Xudong Dong; Yueru Ma; Kaiqi Nie; Jiahui Shen; et al. (Nature Communications)
Abstract Plasmonic photocatalysis enabled by the unique localized surface plasmon resonance represents a promising approach for efficient solar energy conversion. Elucidating the distinct plasmonic catalytic mechanisms and quantification of their effect is crucial yet highly challenging, due to their complex and synergistic nature. Herein, we achieve the differentiation and quantification of thermal as well as various non-thermal reaction mechanisms in prototypical Au-[Fe(bpy)3]2+ antenna-reactor photocatalysts using water splitting as test reaction. Through modification of the resonance condition and connection schemes, non-thermal plasmonic charge and energy transfer mechanisms are selectively shielded. It is found that plasmonic charge carrier-induced photochemistry dominates the photocurrent (~57%) in a reducing, hydrogen evolution environment; whereas resonant plasmonic energy transfer dominates (~54%) in an oxidative, oxygen evolution environment. Our approach provides generalized and fundamental understandings on the role of surface plasmons in photocatalysis as well as important design principles for plasmonic photocatalysts towards distinct reaction types and catalyst configurations.